Elbow movement detection using brain computer interface - Farid, Ghani, Prof. Dr.; Jilani, Musfira; Raghav, Mohit; Farooq, Omar; Yusuf Uzzama, Khan (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org